Viral Diseases of Cultured Penaeus Semisulcatus De Haan with Emphasis on Control Measures of Penaeus Monodon Baculovirus (MBV) In the Islamic Republic Of Iran - Tokhmafshan, Mohammad (2001)
Shrimp aquaculture in Islamic Republic of Iran has a short history. Farmed shrimp production grew slowly from 1992 until 2000 when a number of large farms started to begin production. In 2000, the production was 4,500 MT and estimated that more than 7,000 MT will be produce by 2001. The present study was carried out to investigate the status of viral shrimp diseases and their impact on the shrimp industry in the I. R. Iran. From August 1997 to March 1998, about two thousand samples of cultured Penaeus semisulcatus postlarvae and subadults were collected from five hatcheries and 20 growout farms distributed in three provinces along the coast of Persian Gulf and Oman Sea. baculovirus was infective at salinity ranging from 5-40 ppt whereas at pH 3 and 12, MBV was completely inactivated. MBV were not affected at pH 5, 7, 8 and 9. Shrimp exposed for 10 hr to MBV at different chlorine concentration (5, 25, 50, 100 and 200 ppm) showed that MBV was completely inactivated after 10 hr of exposure to 200 ppm. Formalin in concentration ranging from 0-100 ppm had no virucidal effect on the infectivity of MBV.